Exhausted CD4+ T cells during malaria exhibit reduced mTORc1 activity correlated with loss of T-bet expression - Villegas-Mendez, A; Khandelwal, G; McGowan, LM; Dookie, RS; Haley, MJ; George, C; Sims, D; Lord, GM; Sinclair, LV; Jenner, RG; Couper, KN (American Association of Immunologists, 2020)
CD4+ T cell functional inhibition (exhaustion) is a hallmark of malaria and correlates with impaired parasite control and infection chronicity. However, the mechanisms of CD4+ T cell exhaustion are still poorly understood. In this study, we show that Ag-experienced (Ag-exp) CD4+ T cell exhaustion during Plasmodium yoelii nonlethal infection occurs alongside the reduction in mammalian target of rapamycin (mTOR) activity and restriction in CD4+ T cell glycolytic capacity. We demonstrate that the loss of glycolytic metabolism and mTOR activity within the exhausted Ag-expCD4+ T cell population during infection coincides with reduction in T-bet expression. T-bet was found to directly bind to and control the transcription of various mTOR and metabolism-related genes within effector CD4+ T cells. Consistent with this, Ag-expTh1 cells exhibited significantly higher and sustained mTOR activity than effector T-bet- (non-Th1) Ag-expT cells throughout the course of malaria. We identified mTOR to be redundant for sustaining T-bet expression in activated Th1 cells, whereas mTOR was necessary but not sufficient for maintaining IFN-γ production by Th1 cells. Immunotherapy targeting PD-1, CTLA-4, and IL-27 blocked CD4+ T cell exhaustion during malaria infection and was associated with elevated T-bet expression and a concomitant increased CD4+ T cell glycolytic metabolism. Collectively, our data suggest that mTOR activity is linked to T-bet in Ag-expCD4+ T cells but that reduction in mTOR activity may not directly underpin Ag-expTh1 cell loss and exhaustion during malaria infection. These data have implications for therapeutic reactivation of exhausted CD4+ T cells during malaria infection and other chronic conditions.